PELATIHAN PENGEMASAN SOUVENIR DAN PENJELASAN SIMULASI PENJUALAN ONLINE DEMI MENINGKATKAN KREATIVITAS, MEMUNCULKAN INOVASI, DAN MEMBERIKAN MOTIVASI UNTUK MEMULAI UMKM BARU - Rani Septiani Sukandar; Apriansyah Sarif; Feronika Alifiatus Sholihah; Lisda Khaerunnisa (Batara Wisnu : Indonesian Journal of Community Services, 2021)
Residents of Banjarsari Village, Kec, have successfully produced several products. Kaduhejo, Pandeglang. However, it lacks innovation and creativity in its packaging. Based on the results of discussions with young women, it was found that there is a need for training so that residents become more creative and innovative in processing products that have been produced by many residents so far, one of which is emping melinjo. From the discussion results, information was also obtained that there were no villagers who had innovative and creative souvenir packaging activities. The opportunity to open a souvenir business is still huge to generate profits amid the current pandemic conditions. To help find solutions to these problems, Bina Bangsa University lecturers and students do community service through souvenir packaging training to explain online sales simulations through e-commerce applications. This service aims to improve the quality of human resources and generate motivation to start new MSMEs that are more innovative and creative while still providing a positive influence on independent business products that already exist in the community. The methods used are coordination, training, mentoring, follow-up plans, and reflection. The process of implementing this work program is gradual, continuous, and sustainable. The results of the souvenir packaging training activities have a positive impact. Not only can we produce creative and unique souvenir packaging, but the trainees can also have the experience of doing photo sessions for root products that look attractive when promoted online. In addition, the training participants were explained about sales simulations through e-commerce applications. The discussion results before the training started showed that the participants had never been and had not been able to package souvenirs at first. However, in the interview after the training was carried out, namely the reflection stage, it was concluded that 100% of the participants could do souvenir packaging creatively and innovatively. In addition, 40% of them can understand product sales simulations through e-commerce applications. So that this souvenir packaging training can be a recommendation as a medium to increase creativity, bring up innovation, and motivate to start new MSMEs.